The environmental debate a documentary history, with timeline, glossary and appendices - Neimark, Peninah 1938-; Mott, Peter Rhoades (Gale virtual reference library, 2011)
Examines the evolution of concern about environmental degradation, pollution, and resource conservation in America from the Colonial period to the present.